Christian Iconography Adorning Corinthian Capitals in Syria - Ahmad Dawa (Studies in Ancient Art and Civilization)
This article explores the additional decorative elements incorporated by Christians onto Corinthian capitals found in various museums in the Syrian Arab Republic, dating back to the Byzantine era (4th–7th centuries). It outlines the symbolic significance of these elements, tracing their historical and religious contexts. The study highlights the diverse forms of crosses present on the capitals, ranging from the equal-armed cross encircled by various frames to Latin crosses and crosses formed by the contiguous folioles of acanthus leaves. Garlands, with various interpretations, emerged in Christian art and are depicted as leafy swags on the Corinthian capitals, featuring different designs. Additionally, the rare representation of grapevines, which held significant importance in Christian symbolism, connects them to biblical narratives and theological concepts. Overall, these elements could aid in dating unidentified Corinthian capitals in the area of study when analyzed alongside other components of the capital.